THE MEDIATING EFFECT OF CUSTOMER EXPERIENCE IN THE RELATIONSHIP BETWEEN EMOTIONAL LABOR AND WORD-OF-MOUTH - Dong Zhan Wu, (PEOPLE: International Journal of Social Sciences, 2025)
Emotional labor plays a crucial role in creating customer perceptions and behaviors in the service industry. This study examines the mediating effect of customer experience on the relationship between emotional labor and word-of-mouth (WOM). Drawing on theoretical frameworks related to emotional labor and customer experience, we propose that frontline employees' emotional efforts influence customer perceptions, which in turn affect their willingness to engage in WOM. This study used PLS (a partial least squares technique), questionnaires were distributed online, and a total of 250 valid questionnaires were collected using convenient sampling, targeting people who have been to retail, catering, or hotel industries within three months. Our findings reveal that customer experience mediates the relationship between deep acting on WOM, highlighting the importance of managing customer interactions effectively. These insights provide valuable implications for service management and marketing strategies aimed at enhancing customer satisfaction and positive WOM.